مهنة المحاماة في دولة المالديف دراسة تقويمية في ضوء الفقه الإسلامي‏ - علي زاهر بن سعيد قاسم (al-Jami'ah al-Islamiyah al-'Alamiyah bi Maliziya, 2008)
This research is an evaluation of the profession of advocacy in the Maldives with reference to Islamic fiqh. In this regard, the researcher compares the profession of advocacy as endorsed in the Maldivian Laws with that in Islamic fiqh. In the second chapter of the study, the researcher defines the profession of advocacy and offers a brief history of the subject. As explained in this chapter, the profession of advocacy is not a new concept. In fact, it was even practiced in ancient times. In Islam, it is called al-wakÉlah bil-kÍuÎËmah. There are similarities and differences between the profession of advocacy in Islam and other manmade systems of law. Although permissible, it has created some dispute among Islamic scholars; the researcher presents his stand on the case after investigating the verdicts available on both sides. The research also discusses and evaluates the compensation of lawyers in the Maldives pertaining to Islamic fiqh. Among other things, the researcher further discusses the pillars and conditions of the profession of advocacy in both Maldivian Law and Islamic fiqh. The moral obligations and conducts, rights and responsibility of lawyers in Maldivian Law, along with how a profession of advocacy contract is formed and concluded are also discussed and evaluated in terms of fiqh. The researcher notes the required legal judgments while advocating in the Maldives and evaluates the practice using fiqh teachings. This evaluation is done by comparing the fiqh standards for the profession of advocacy. The research methodology used is mainly description and discussion based on comparison. The researcher has brought forth the views of the different schools of fiqh on the subject matter — the profession of advocacy. Additional discussions and details are included along with the researcher’s view on issues related to the subject. Finally, an overall evaluation of the way the profession of advocacy is carried out in the Maldives and the laws stipulating the matter are put forward in the light of fiqh.